"FROM COAL TO COOL": THE CREATIVE CLASS, SOCIAL CAPITAL, AND THE REVITALIZATION OF SCRANTON. Issue 3 (27th September 2012) - RICH, MEGHAN ASHLIN
Abstract : ABSTRACT: This study examines the processes of revitalization within small cities, using Scranton, a postindustrial city in Northeast Pennsylvania, as a case study. Through qualitative interviews, I examine the motivation factors for key players in the revitalization of Scranton's downtown, such as business owners, city and nonprofit administrators, and cultural leaders. Revitalizers are heavily influenced by Richard Florida's creative class theory in that they strongly believe that promoting arts and culture and creating a consumer‐based downtown is imperative for urban renewal. However, revitalizers are also motivated because Scranton has a high level of social capital, especially in terms of bonding capital. Strong social ties (including community, family, and institutional) assist revitalizers in their creative endeavors. This study indicates that small cities attempting to achieve economic and population stability should focus on their strengths: city livability and the thick social ties that maintain communities.